0247 Sleep Disturbance is Associated with Dysregulation of Positive and Negative Affect Systems. (25th May 2022) - Stepan, Michelle; Buysse, Daniel; Siegle, Greg; Hasler, Brant; Soehner, Adriane; Franzen, Peter
Abstract: Introduction: Sleep disturbance is a risk factor for the development of mood disorders and up to 90% of mood disorder patients report sleep problems. However, the neural mechanisms by which poor sleep contributes to mood disorders are not well understood. We investigated whether sleep disturbance was associated with dysregulation of positive and negative affect systems, including passive reactivity and active emotion regulation. Methods: Participants (n=55, Mage=24.4 years, 53% female) selected for high, medium, and low scores on the PROMIS Sleep Disturbance scale completed a cognitive reappraisal task in an fMRI scanner. Participants were presented with International Affective Picture Stimuli (30 positive, 30 negative, 15 neutral) and were instructed to either passively view or actively up- or down-regulate their emotional experience. We tested five conditions: view-positive, upregulate-positive, view-negative, downregulate-negative, view-neutral. Participants also completed objective (i.e., 7-day actigraphy) and self-report (i.e., Insomnia Severity Index [ISI]) measures of sleep prior to the scan. Analyses in AFNI were constrained within an emotion regulation network, identified using a Neurosynth mask, and treated as a single region of interest. Voxelwise (puncorr<.005) and clusterwise thresholds (p<.05) were used to correct for multiple comparisons. Results: Actigraphy-assessed sleep duration was associated with supplementary motor area (SMA) activity when upregulating positive affect relative to passively viewing positive images (k=44 voxels, clusterwise p=.04); participants who slept less showed greater SMA activity. ISI score was marginally associated with dorsolateral prefrontal cortex (dlPFC) activity when downregulating negative affect relative to an implicit baseline (k=30 voxels, clusterwise p=.10); individuals with greater insomnia severity showed more dlPFC activity. PROMIS Sleep Disturbance showed no significant associations. Conclusion: Markers of poor sleep (i.e., lower sleep duration, greater insomnia severity) were associated with heightened SMA and dlPFC activity during cognitive reappraisal. This may suggest inefficiency in modulating positive affect via verbal and motor processes (i.e., SMA) and negative affect via cognitive control (i.e., dlPFC). Alternatively, individuals with poor sleep may have greater emotional reactivity to modulate. Mood disorders are commonly associated with increased negative affect and blunted positive affect. Our findings suggest a plausible neural substrate for how sleep disturbance contributes to dysregulation of these systems. Support (If Any): NIMH R21 MH102412.